Charlemagne The life and times of an early medieval emperor - Bhote, Tehmina (New York The Rosen Publishing, 2005)
Discusses the life and reign of Charlemagne, king of the Franks, ruler of a united Western Europe.
includes bibliographical references and index
10 - 12 years
Keywords: Charlemagne, Emperor -- 742-814; Kings and rulers -- France -- Biography; Holy Roman Empire -- Kings and rulers -- Biography; History -- France -- To 987; Holy Roman Empire -- History -- To1517